Arsenic Toxicity: The Effects on Plant Metabolism - Finnegan, Patrick; Chen, Weihua (Frontiers in Physiology, 2012)
The two forms inorganic arsenic, arsenate (AsV) and arsenite (AsIII), are easily taken up by the cells of the plant root. Once in the cell, AsV can be readily converted to AsIII, the more toxic of the two forms. AsV and AsIII both disrupt plant metabolism, but through distinct mechanisms. AsV is a chemical analogue of phosphate that can disrupt at least some phosphate-dependent aspects of metabolism. AsV can be translocated across cellular membranes by phosphate transport proteins, leading to imbalances in phosphate supply. It can compete with phosphate during phosphorylation reactions, leading to the formation of AsV adducts that are often unstable and short-lived. As an example, the formation and rapid autohydrolysis of AsV-ADP sets in place a futile cycle that uncouples photophosphorylation and oxidative phosphorylation, decreasing the ability of cells to produce ATP and carry out normal metabolism. AsIII is a dithiol reactive compound that binds to and potentially inactivates enzymes containing closely spaced cysteine residues or other sulfhydryl-containing groups. Arsenic exposure generally induces the production of reactive oxygen species that can lead to the production of antioxidant metabolites and numerous enzymes involved in antioxidant defense. Oxidative carbon metabolism, amino acid and protein relationships, and nitrogen and sulfur assimilation pathways are also impacted by As exposure. These effects are reflected in a dramatic restructuring of amino acid pools in Arabidopsis thaliana upon AsV exposure. Readjustment of several metabolic pathways, such as glutathione production, has been shown to lead to increased arsenic tolerance in plants. Species- and cultivar-dependent variation in arsenic sensitivity and the remodeling of metabolite pools that occurs in response to As exposure gives hope that additional metabolic pathways associated with As tolerance will be identified.